THE INFLUENCE OF INTERACTIVE WHITEBOARD USE AT VOCATIONAL SUBJECTS ON TEACHER extasciiacuteS AUTHORITY - PODARIL, Martin; RUSNAKOVA, Sona; Roman, HRMO (Trends in education, 2014)
The implementation of modern technologies into the educational process not only brings problems and worries, but also the possibility of using non-traditional methods of teaching. By this implementation, teachers get a powerfull tool and therefore they should learn how to use it properly. Research part is focussed on the influence of interactive whiteboard use on teacher extasciiacutes authority.
Keywords: interactive whiteboard; modern technologies; teacher extasciiacutes authority; vocational subjects.